Theoretical and experimental spectroscopic studies of the first highly luminescent binuclear hydrocinnamate of Eu(III), Tb(III) and Gd(III) with bidentate 2,2 '-bipyridine ligand - Marques, Lippy F.; Correa, Charlane C.; Garcia, Humberto C.; Francisco, Thiago Martins; Ribeiro, Sidney José Lima [UNESP]; Dutra, Jose Diogo L.; Freire, Ricardo O.; Machado, Flavia C. (Elsevier B.V., 2014)
In this paper, the synthesis of three new binuclear lanthanide (III) complexes [Ln(2)(cin)(6)(bpy)(2)] (Ln=Eu (1), Tb (2), Gd (3), cin=hydrocinnamate anion; bpy=2,2'-bipyridine), and their complete characterization, including single crystal X-ray diffraction, FTIR spectroscopy and thermal analysis (TGA/DTA) are reported. In especial, photophysical properties of Eu(III) complex have been studied in detail via both theoretical and experimental approaches. Crystal structures of 1-3 reveal that all compounds are isostructural and that each lanthanide ion is nine-coordinated by oxygen and nitrogen atoms in an overall distorted tricapped trigonal-prismatic geometry. Eu(III) complex structure was also calculated using the Sparkle model for lanthanide complexes and the intensity parameters (Omega(2), Omega(4), and Omega(6)), calculated from the experimental data and from Sparkle/PM3 model. The theoretical emission quantum efficiencies obtained for Sparkle/PM3 structures are in excellent agreement with the experimental values, clearly attesting to the efficacy of the theoretical models. The theoretical procedure applied here shows that the europium binuclear compound displays a quantum yield about 65% suggesting that the system can be excellent for the development of efficient luminescent devices. (C) 2013 Elsevier By. All rights reserved.
Keywords: Lanthanides; Hydrocinnamic acid; Photophysical studies